PENGEMBANGAN WISATA TEMATIK BERBASIS KULINER DI DESA WISATA SERANGAN - I Made Trisna Semara; AA. Ayu Arun Suwi Arianty (Jurnal IPTA (Industri Perjalanan Wisata), 2022)
Serangan Village is one of the tourist villages in Denpasar City. Serangan Tourism Village faces quite tough tourism challenges. The challenge is not maximizing local products as a tourist attraction. The purpose of this research is to develop the concept of culinary-based thematic tourism in Serangan Tourism Village. The development of the thematic tourism concept is expected to encourage the development of Serangan Village as a tourist village by developing local food to become a tourist attraction. This concept is able to respond to global tourism trends and as a preservation of local cultural values. So that a tourist attraction will appear in the form of a culinary tour with the characteristics of Serangan Village or Bali in general. The research method uses a qualitative descriptive approach.